Development and analyses of a lever system for a newly designed self-equalising thrust bearing. (July 2022) - Monkova, Katarina; Urban, Marek; Moravka, Stefan; Monka, Peter Pavol; Božić, Željko
Highlights: The misalignment of the rotor relative to the stator in rotary machines affects the safe operability of the bearings. For maximum misalignment compensation, a bearing development with a newly designed lever system was developed. Stress, contact and stiffness analyses confirmed the appropriate geometry of the lever design made of 34CrNiMo6 steel. Verifications of complete bearings under operating conditions confirmed their good functionality and reliability. Abstract: Thrust bearings are undoubtedly one of the essential parts of turbines and compressors. However, there are many cases in which asymmetric load occurs on the bearings due to e.g. thermal deformations, production inaccuracies or a simple deflection of the shaft. The presented research deals with some basic steps involved in comprehensive research related to developing a new self-equalising thrust bearing. It focuses on the design of its most crucial part - lever, which is responsible for the proper equalising functionality. The study aimed to design a new type of lever geometry, create its numerical model, and, through numerical analysis and calculations, predict its useability in real conditions. According to von Mises hypothesis, stresses were evaluated, as well as contacts and stiffness according to Hertz's theory. The lever was modelled in two sizes, which suit the bearings representing the most often used types in powerful machines. For the levers' design and production, the steel 34CrNiMo6 has been used in a refined state with a yield strength of 900 MPa. The results achieved within the experimental static tests and verifications in operating conditions confirmed the correctness of the final geometry design of the levers, its sufficient stiffness, as well as good functionality of the thrust bearing and its reliability.